2015
DOI: 10.1007/s10014-015-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

A case of cerebral astroblastoma with rhabdoid features: a cytological, histological, and immunohistochemical study

Abstract: The Ki-67 labeling index was 10.8%. This tumor was finally diagnosed as low-grade astroblastoma and the patient had no evidence of recurrence without postoperative radiotherapy or chemotherapy during the last 6 months of follow-up. This report describes novel cytological, histopathological, and immunohistochemical features of the rare tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Intriguingly, these tumors share some clinical, histologic and molecular features: both tumors showed a pathogenic TP53 mutation, numerous whole chromosome copy number alterations, occurred in adult patients and had an epithelioid/rhabdoid morphology with some discohesive cells. This histologic pattern has been described in several astroblastoma case reports (in addition to one included in this study) and could be associated with a favorable prognosis, as we saw in our cases . Surprisingly, neither DNA methylation profiling nor FISH suggested that these two tumors have an MN1 alteration, although we cannot exclude the possibility of an MN1 abnormality that cannot be detected by breakapart FISH in these cases.…”
Section: Discussionsupporting
confidence: 70%
“…Intriguingly, these tumors share some clinical, histologic and molecular features: both tumors showed a pathogenic TP53 mutation, numerous whole chromosome copy number alterations, occurred in adult patients and had an epithelioid/rhabdoid morphology with some discohesive cells. This histologic pattern has been described in several astroblastoma case reports (in addition to one included in this study) and could be associated with a favorable prognosis, as we saw in our cases . Surprisingly, neither DNA methylation profiling nor FISH suggested that these two tumors have an MN1 alteration, although we cannot exclude the possibility of an MN1 abnormality that cannot be detected by breakapart FISH in these cases.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, in contrast to ependymomas, the spaces between the pseudorosettes were often rari ed. EMA expression was previously shown to be typically localized at the cell membrane in astroblastomas [22][23][24], which was also observed in our patient. In ependymoma, EMA is expressed along the luminal surface of some ependymal rosettes or manifests as dot-like perinuclear or ring-like cytoplasmic structures [25].…”
Section: Discussionsupporting
confidence: 87%
“…Eight cases, microscopic features of which meet the diagnostic criteria of astroblastoma defined by the 2016 WHO CNS tumor classification , were selected from the pathology files of the institutes of the authors. Two (Cases 3 and 6) have already been reported elsewhere . This research was approved by the Ethics Committee of Gunma University.…”
Section: Methodsmentioning
confidence: 99%